Redefining Corporate Tax Avoidance through Strategic Sustainability Issues - Dewi W. Octaviani; Agustin Fadjarenie; Catur Widayati; Deden Tarmidi (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study investigates the impact of corporate sustainability practices—specifically ESG performance, renewable energy adoption, and sustainability-oriented tax strategies—on tax avoidance within Indonesia’s energy sector. It explores the intersection between fiscal strategy and environmental governance in addressing ethical and sustainability-related challenges in corporate behavior. A mixed-methods approach was employed to gain a comprehensive understanding: the quantitative component analyzed 464 firm-year observations, while the qualitative component involved semi-structured interviews with five key informants, including tax professionals and sustainability managers. The quantitative results reveal that firms with stronger ESG engagement, higher proportions of renewable energy usage, and lower effective tax rates tend to exhibit lower levels of tax avoidance. These findings are reinforced by qualitative insights, which indicate that ethical values, reputational concerns, and organizational transparency significantly influence managerial tax decisions. However, inconsistent fiscal incentives and regulatory uncertainties in Indonesia remain major barriers to integrating sustainability into corporate tax strategies. This study contributes to the literature by reframing tax avoidance not merely as a legal or financial matter, but as a strategic sustainability issue embedded in corporate governance and operations. It offers practical policy implications, highlighting the need for coherent and targeted fiscal incentives to support the clean energy transition and ethical tax conduct in emerging economies. Keywords: Tax Avoidance; ESG Performance; Renewable Energy; Sustainability Governance; Mixed-Methods Approach.